2018
DOI: 10.1002/app.46599
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of fully bio‐based flame retardant poly(lactic acid) composites containing casein

Abstract: In this work, a bio‐based flame retardant, casein, was incorporated into poly(lactic acid) (PLA) matrix by melt compounding in order to improve the fire resistance and sustain the biodegradable character of PLA simultaneously. The fire performance of PLA composites was evaluated by limiting oxygen index, UL‐94 vertical burning, and cone calorimeter tests, respectively. The results indicated that the introduction of 20% casein increased the limiting oxygen index value of PLA composites from 20.0% to 32.2%, upgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…The PLA composites achieved a UL94 V-0 rating upon addition of 20-30 wt.% of one of these biomass derived compounds. [20][21][22][23][24][25] Xuan et al synthesized melamine salts of bicyclic pentaerythritol phosphate alcohol (IFR-I and IFR-II). The incorporation of the new compounds in PLA improved the flame retardancy, reaching a V-0 classification with 20 wt.% addition in the best case.…”
Section: Introductionmentioning
confidence: 99%
“…The PLA composites achieved a UL94 V-0 rating upon addition of 20-30 wt.% of one of these biomass derived compounds. [20][21][22][23][24][25] Xuan et al synthesized melamine salts of bicyclic pentaerythritol phosphate alcohol (IFR-I and IFR-II). The incorporation of the new compounds in PLA improved the flame retardancy, reaching a V-0 classification with 20 wt.% addition in the best case.…”
Section: Introductionmentioning
confidence: 99%
“…They were not as marked as the PET-only fabrics'-but exhibited no dripping, as the PET did; see Table 2. Casein has also been shown to be an effective flame retardant when incorporated into poly(lactic acid) [42]. blends at 20 wt % loadings.…”
Section: Proteinsmentioning
confidence: 99%
“…They were not as marked as the PET-only fabrics'-but exhibited no dripping, as the PET did; see Table 2. Casein has also been shown to be an effective flame retardant when incorporated into poly(lactic acid) [42]. Gelatins, derived from bovine or fish sources, have been shown to reduce flammability in some polymer systems, including poly(vinyl alcohol) and polyolefins [43,44].…”
Section: Proteinsmentioning
confidence: 99%
“…However, most of the existing flame retardants are made from petroleum‐based materials, and developing biobased materials is helpful to increase the recyclability of PLA. Some biomacromolecules can be directly used as flame retardants of PLA, for example chitosan (CS), casein, lignin, and deoxyribose nucleic acid (DNA) 24–27 . Chen et al 24 added CS and ammonium polyphosphate (APP) into PLA directly.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that 2 wt% CS and 5 wt% APP can make PLA achieve the UL‐94 V‐0 rating with an increased LOI of 33.1%. Zhang et al 25 used casein to modify PLA. It was found that 20 wt% casein could increase the LOI of PLA composite from 20.0 to 32.2% and achieve the UL‐94 V‐0 rating.…”
Section: Introductionmentioning
confidence: 99%